A community-centric model for conference co-creation: the world conference on CDG for patients, families and professionals - Rita Francisco; Carlota Pascoal; Pedro Granjo; Claudia de Freitas; Paula A. Videira; Vanessa dos Reis Ferreira (Research Involvement and Engagement, 2024)
Abstract Background Patient and public co-creation and involvement in health initiatives have been witnessing great expansion in recent years. From healthcare to research settings, collaborative approaches are becoming increasingly prevalent and diverse, especially in the field of rare diseases which faces complex challenges. Conference development and implementation, however, have been primarily guided by passive, information-sharing models. There is a need for conferences to evolve towards more inclusive, interactive, collaborative, and problem-solving platforms. Here, we aimed to report on a pioneer model, emphasizing a community partnership approach to conference co-creation that takes the World Conference on Congenital Glycosylation Disorders (CDG) as an exemplary case. Methods To answer the need to overcome the lack of access to high-quality information which limits CDG diagnosis, research and treatment options, the World CDG Organization has been refining a community-centric model for conference co-creation. Focusing on the 5th edition of the conference, data on stakeholders’ preferences was collected using an online survey and a poll to define the conference agenda, guide its development and select optimal dates for an all-stakeholder inclusive, relevant and participatory event. Results We describe the complexities of the community-centric conference co-creation model, detailing its refined methodology and the outcomes achieved. The model is grounded on a participative approach to promote people-centered research and care for CDG patients. The involvement of the public in the conference co-creation and in participatory methods allowed the generation of knowledge on community needs and preferences. Conclusion This paper describes a reliable, highly adaptable conference co-creation model that fosters community-building, disseminates understandable information, and serves as a borderless platform to incentivize multiple stakeholder collaborations towards CDG research and drug development. We argue this is a reproducible model that can be endorsed and more widely adopted by other disease communities and events.